Psychotic spectrum features in borderline and bipolar disorders within the scope of the DSM-5 section III personality traits: a case control study - Henriques-Calado, Joana (2023)
Background Psychotic spectrum features in borderline personality disorder (PD) are a long-standing phenomenon, but remarkably, to date, they have not been the focus of many empirical studies. Moreover, the comparative studies that acknowledge their links to afective psychoses are even more scarce. Likewise, the contributions of empirical research on the DSM-5 dimensional approach to this topic are also uncommon. This study seeks to identify the best set of pathological personality traits and/or symptoms that are predictors of psychotic features (psychoticism and ideation paranoid symptoms) in borderline PD and in bipolar disorder, based on the framework of the DSM-5 section III personality traits. Methods A cross-sectional study of two clinical samples: 1) Borderline PD group of 63 participants; 2) Bipolar disorder group of 65 participants. Self-reported assessment: Personality Inventory for DSM-5 (PID-5); Brief Symptom Inventory (BSI). A series of linear and logistic regression analyses were computed. Results Overall, the data emerging as common predictors are detachment, negative afectivity, psychoticism, depressivity, grandiosity, suspiciousness and interpersonal sensitivity symptoms. Borderline PD has the highest score in BSI paranoid ideation which emerges as its discriminating trait (Nagelkerke R2=.58): cognitive and perceptual dys‑ regulation (OR: 13.02), restricted afectivity (OR: 12.09), withdrawal (OR: 11.70), anhedonia (OR: 10.98) and emotional lability (OR: 6.69). Conclusions Besides the commonality that appears to overlap both disorders with a psychosis superspectrum, the patterns of the pathological personality-symptoms underlying the psychotic features appear to reinforce a position between schizophrenia and bipolar disorders that borderline PD may occupy, highlighting the possibility of its inter‑ section with schizoafective/psychosis spectra. The pathological personality nature of the psychotic features emerges as a potential comprehensive trait of the phenomenological dimensions.